108 Effects of post-weaning supplementation of immunomodulatory feed ingredient on cortisol concentrations and microbial populations in programmed fed beef heifers. (29th July 2019) - McCarty, Keelee J; Tipton, Jessie; Ricks, Ralph; Danielo, Jessica L; Thompson, Jesse; Long, Nathan
Abstract: The objective was to determine the effects of immunomodulatory feed ingredient during post-weaning on cortisol concentration and fecal microbial populations of beef heifers. Commercial Angus heifers (n = 72) from two AI sires were blocked (n = 9) by sire and BW, randomly assigned to one of two pens (4 heifers/pen) per block, then assigned to treatments. Heifers were fed twice daily from d 0 to 60 (gain 0.75 kg/day) and top-dressed once daily with either 72g of Celmanax (CEL) or corn germ (CON; corn germ meal) per pen. After 60 days, two heifers per pen (n = 32) were randomly selected for a transportation challenge. Fecal grab samples were collected on d 0 and 69 of treatment, hr -24, 0, 24 of the challenge and 7 d post-challenge. Serum samples were collected at h 0, 4, 8, and 12 of the challenge. Clostridia and E. coli were enumerated from fecal samples using selective media. Isolates (≤ five isolates from each media per sample) were genetically tested to determine if they were C. perfringens or pathogenic E. coli. Fecal samples were enriched for detection of Salmonella. Pen was the experimental unit and data was analyzed by ANOVA or repeated measures analysis. Following treatment, decreased (P ≤ 0.05) populations of total E. coli, Salmonella, and C. perfringens were observed in CEL heifers compared to CON heifers, whereas clostridia and pathogenic E. coli were not different (P > 0.05) between treatments. Transportation stress increased (P ≤ 0.05) populations of clostridia, C. perfringens, total E. coli, and Salmonella, but decreased (P = 0.0252) pathogenic E. coli counts. Cortisol concentrations were decreased (P < 0.05) in CEL heifers compared to CON heifers throughout the challenge. In summary, supplementation of Celmanax post-weaning altered microbial populations and cortisol concentrations were reduced during transportation in beef heifers.